Assembly and manipulation of responsive and flexible colloidal structures by magnetic and capillary interactions. Issue 14 (22nd March 2023) - Basu, Abhirup; Okello, Lilian B.; Castellanos, Natasha; Roh, Sangchul; Velev, Orlin D.
Abstract : The long-ranged interactions induced by magnetic fields and capillary forces in multiphasic fluid–particle systems facilitate the assembly of a rich variety of colloidal structures and materials. Abstract : The long-ranged interactions induced by magnetic fields and capillary forces in multiphasic fluid–particle systems facilitate the assembly of a rich variety of colloidal structures and materials. We review here the diverse structures assembled from isotropic and anisotropic particles by independently or jointly using magnetic and capillary interactions. The use of magnetic fields is one of the most efficient means of assembling and manipulating paramagnetic particles. By tuning the field strength and configuration or by changing the particle characteristics, the magnetic interactions, dynamics, and responsiveness of the assemblies can be precisely controlled. Concurrently, the capillary forces originating at the fluid–fluid interfaces can serve as means of reconfigurable binding in soft matter systems, such as Pickering emulsions, novel responsive capillary gels, and composites for 3D printing. We further discuss how magnetic forces can be used as an auxiliary parameter along with the capillary forces to assemble particles at fluid interfaces or in the bulk. Finally, we present examples how these interactions can be used jointly in magnetically responsive foams, gels, and pastes for 3D printing. The multiphasic particle gels for 3D printing open new opportunities for making of magnetically reconfigurable and "active" structures.